Pathology and diagnosis of ocular squamous cell carcinoma in bovines - Kumar, Vivek; Jolhe, Dhananjay Kumar; Ghosh, Ratan Chandra; Sonkusale, Prashant M; Sharma, Sonu (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
This study revealed the pathomorphological features and immunohistochemical expression of Pan-cytokeratin (Pan-CK), p53, epidermal growth factor receptor (EGFR) and p16 in 6 clinical cases of neoplasms of eye in bovines suspected of ocular squamous cell carcinoma (OSCC). Three out of 6 cases (50%) were confirmed as OSCC on the basis of histopathological and immunohistochemical analysis. Two cases were confirmatory in Holstein Friesian and 1 in Murrah buffalo. Grossly unilateral large firm cauliflower like mass, extending deep into frontal and nasal sinuses, congested with verrucous surface, large reddish protruded mass covering the whole cornea with severe hemorrhage resulted in blindness. Large nodular, hemorrhagic growth on limbus and lower eyelid with verrucous surface was also observed. OSCCs were classified into well, moderately and poorly differentiated types on the basis of histopathology and immunohistochemistry (IHC). Histopathological findings in OSCC were distinctive keratin pearls with concentric layers of keratinization observed in well differentiated OSCC. Absence of epithelial pearls although numerous mitotic figures along with evidences of anaplasia and neovascularization were observed in poorly differentiated OSCC, moderate degree of keratinization with keratin deposition at the center of neoplastic islets in moderately differentiated OSCC. Highest immunohistochemical expression was observed in Pan-CK which confirmed the tumours were of epithelial origin and EGFR was confirmatory for malignancy and degree of metastasis. Expression of Pan-CK in well differentiated OSCC revealed strong immunoreactivity towards Pan-CK. High immunoreactivity against EGFR with strong expression of EGFR in moderately differentiated OSCC and mild immunoreaction in poorly differentiated OSCC. Mild immunopositive reaction for p16 observed in one case. Neoplasms of eye can be confirmed as OSCC by immunoexpression of Pan-CK, EGFR, p16 and p53 in malignant tumours including both well and moderately differentiated OSCC.